KEANEKARAGAMAN SPESIES BURUNG DI LANSKAP AGROFORESTRI ILENGI - Hiola, Abdul Samad; -, Bachtiar (Gorontalo Journal of Forestry Research, 2018)
Bird Species dependsonlandscape,whichisusedastheir breeding,  restingand feeding area.  Landscape of Agroforestry Ilengiis  mix tree garden like primer forest.Thisstudy is aim togather informationaboutdiversity bird species,including richness, evennessandspeciessimilarity oneachlocationinthestudy.Thisstudy used concentrationmethod. Eightspeciesofbirdsand194 countwerefoundduring3monthsstudy.Thehighestdiversity valuewasfoundin landscape agroforestry ilengi 1,29. Generally bird diversity in all location research include medium level. The richness of species is highest at natural forests with a value 1.70. Evenness of bird species in agroforestry ilengi in the category unstable. The role of local communities for conservation is good enough to understand the habits of birds in agroforestry ilengi, such Local naming each of the birds found 61% of respondents know about the birds in the research sites.